COVID-19 pandemic impact on new economy development and societal change - Popescu, Cristina Raluca Gh., 1983- (Advances in finance, accounting, and economics (AFAE) book series., 2022)
"This book highlights the newest trends, novel practices and latest tendencies concerning the manner of shaping the new economy and accelerating societal change, in the attempt to demonstrate the crucial importance of rethinking the world's models, priorities, and strategies generated by the important changes caused by the Covid-19 pandemic shock"--